Social Media and Clinical Trials in Pediatric Disease: Musings From the Bench - Nelson, Leslie; Iannaccone, Susan T. (Frontiers in Genetics, 2021)
The use of social media in clinical trials, for recruiting and retention as well as for collecting data, has become increasingly common. However, little has been documented in respect to the guidelines for its use and the possible effects it may have on clinical trials. In this review, we provide an overview of the guidance that has been published and muse the pros and cons of the use of social media in trials for rare disease.